Smart Daylighting Strategies for Architectural Studios: Evaluating Louvre Angles and Time Effects Through Revit Simulations - Novia Bramiana Chely; Azzam Ismail Muhammad; Ismail Hasan Muhammad; Mahjuddin Ressang Asrul (E3S Web of Conferences)
This study explores the effectiveness of louvre windows in optimizing daylighting within an architectural studio using Revit simulations. The aim was to enhance natural light distribution, minimize glare, and control heat gain to improve comfort and productivity. Simulations were conducted for a 48 m² west-facing studio, testing louvre angles (0°, 15°, 30°, 45°) at different times of day (7:00 AM, 11:00 AM, 1:00 PM, and 4:00 PM). Results indicate that flatter angles (0° and 15°) maximize early morning daylight but increase glare, while steeper angles (30° and 45°) reduce glare but limit illuminance. At midday, moderate angles (15° and 30°) strike a balance between glare control and daylight distribution. In the afternoon, steeper angles (30° and 45°) effectively manage glare while maintaining adequate daylight. The study underscores the trade-off between illuminance and glare control, essential for visual comfort in studios. Optimized daylighting reduces reliance on artificial lighting, promoting energy efficiency and climate change mitigation. However, limitations such as static simulations and lack of real-world validation highlight the need for further research to confirm findings and explore advanced daylighting strategies.